Integrated specialized atrial fibrillation clinics reduce all-cause mortality: post hoc analysis of a randomized clinical trial. Issue 12 (7th August 2019) - Hendriks, Jeroen M L; Tieleman, Robert G; Vrijhoef, Hubertus J M; Wijtvliet, Petra; Gallagher, Celine; Prins, Martin H; Sanders, Prashanthan; Crijns, Harry J G M
Abstract: Aims: An integrated chronic care programme in terms of a specialized outpatient clinic for patients with atrial fibrillation (AF), has demonstrated improved clinical outcomes. The aim of this study is to assess all-cause mortality in patients in whom AF management was delivered through a specialized outpatient clinic offering an integrated chronic care programme. Methods and results: Post hoc analysis of a Prospective Randomized Open Blinded Endpoint Clinical trial to assess all-cause mortality in AF patients. The study included 712 patients with newly diagnosed AF, who were referred for AF management to the outpatient service of a University hospital. In the specialized outpatient clinic (AF-Clinic), comprehensive, multidisciplinary, and patient-centred AF care was provided, i.e. nurse-driven, physician supervised AF treatment guided by software based on the latest guidelines. The control group received usual care by a cardiologist in the regular outpatient setting. After a mean follow-up of 22 months, all-cause mortality amounted 3.7% (13 patients) in the AF-Clinic arm and 8.1% (29 patients) in usual care [hazard ratio (HR) 0.44, 95% confidence interval (CI) 0.23–0.85; P = 0.014] . This included cardiovascular mortality in 4 AF-Clinic patients (1.1%) and 14 patients (3.9%) in usual care (HR 0.28; 95% CI 0.09–0.85; P = 0.025). Further, 9 patients (2.5%) died in the AF-Clinic arm due to a non-cardiovascular reason and 15 patients (4.2%) in the usual care arm (HR 0.59; 95% CI 0.26–1.34; P = 0.206). Conclusion: An integrated specialized AF-Clinic reduces all-cause mortality compared with usual care. These findings provide compelling evidence that an integrated approach should be widely implemented in AF management.